European capitals of culture and life satisfaction - Lasse Steiner; Bruno S. Frey; Simone Hotz (University of Zurich, Department of Economics, 2013)
This paper analyzes whether hosting the most prestigious European cultural event, the European Capital of Culture, has an impact on regional economic development or the life satisfaction of the local population. Concerning the economic impact, we show that European Capitals are hosted in regions with above average GDP per capita, but do not causally affect the economic development in a significant way. Even a positive impact on GDP per capita would not imply a positive impact on individual utility or social welfare of the regional population. Surprisingly, using difference-in-difference estimations, a negative effect on the well-being of the regional population is found during the event. Since no effect is found before the event, reverse causality and positive anticipation can be ruled out. The negative effect during the event might result from dissatisfaction with the high levels of public expenditure, transport disruptions, general overcrowding or an increase in housing prices.
Keywords: H40; H54; R12; Z11; Z18; 330; Life Satisfaction; Mega-Events; Culture; European Capital of Culture; Stadt; Kulturgüter; Großveranstaltung; Zufriedenheit; Stadtbevölkerung; Stadtentwicklung; EU-Staaten